The role of regulatory T cells in the control of B cell mediated immune responses - Wollenberg, Ivonne, 1976- (2011)
Tese de doutoramento, Ciências Biomédicas (Imunologia), Universidade de Lisboa, Faculdade de Medicina, 2011